Mobile APP for motivation to learning: an engineering case. Issue 8 (16th November 2016) - Jou, Min; Lin, Yen-Ting; Tsai, Hsieh-Chih
Abstract : Synthesis of Materials is regarded as an important core subject in engineering education. However, many concepts and knowledge in the material synthesis can be rather abstract and difficult to understand by the student learners. Experiments are limited in scope due to lack of equipment, control of toxic materials, and risks of chemical reactions, which often restricts student imagination and student involvement in practical training. These reasons often led to poor learning attitude and learning performance among the students. Rapid developments in Cloud technology and mobile devices have provided new opportunities for developing novel learning tools for material synthesis. This study aims to introduce interest factors as a strategy for promoting learning interest and practical skills among the students. Chemical symbols, experimental themes, texts, and interactive elements were utilized to develop a theme-based Mobile Learning APP for teaching the practical techniques of material synthesis. The Mobile Learning APP was then integrated into a problem-based learning activity. A quasi-experimental design was used to investigate the resulting learning effectiveness from using the developed Mobile Learning APP. Results show that the Mobile Learning APP provided a significant positive effect on learning performance and that most students showed favorable attitudes toward the usage of the mobile learning system.